2012
DOI: 10.1093/cvr/cvs299
|View full text |Cite
|
Sign up to set email alerts
|

Early repolarization in mice causes overestimation of ventricular activation time by the QRS duration

Abstract: In the mouse, ventricular myocardium activation and early repolarization waves are simultaneously present. This hampers unequivocal interpretation of the duration of the QRS complex as a measure of ventricular activation duration, especially when conduction is slowed. Under these conditions mapping of local activation and repolarization patterns is required for correct interpretation of the ECG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 31 publications
2
69
1
Order By: Relevance
“…The start of the QRS complex was defined as the earliest moment of deviation from baseline. The end of the QRS complex determined in lead III and was defined as the moment when the S wave returned to the isoelectric line (Boukens et al, 2013). We determined the end of the T wave by the tangent method (Lepeschkin and Surawicz, 1952).…”
Section: Methodsmentioning
confidence: 99%
“…The start of the QRS complex was defined as the earliest moment of deviation from baseline. The end of the QRS complex determined in lead III and was defined as the moment when the S wave returned to the isoelectric line (Boukens et al, 2013). We determined the end of the T wave by the tangent method (Lepeschkin and Surawicz, 1952).…”
Section: Methodsmentioning
confidence: 99%
“…VEGF-B TG hearts show two distinct ECG changes. First is increase in the width of the QRSp which together with unaffected QRS represents prolongation of early repolarization (Liu et al, 2004; Boukens et al, 2013, 2014). That prolongation fits very good to lengthening of APD 60–70 which we observed in TG cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…That change of QRSp is common to LVH (Merentie et al, 2015) and some forms of sodium channelopathies (Remme et al, 2006; Watanabe et al, 2011). And second is decreased amplitude of the R and S waves, which has been shown to associate with acute infarction or ischemia in mouse heart (Gehrmann et al, 2001; Merentie et al, 2015) and e.g., sodium channel blocker Ajmaline (Boukens et al, 2013). VEGF-B TG hearts show only modest signs of organ level hypertrophy and no infarctions, so that the ECG anomalies cannot be considered as signs of cardiac disease, but they rather reflect more specific changes in cardiomyocytes electrophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent investigators defined the end of QRS complex at the end of J-wave [30]. Optical mapping studies showed that ventricular activation in mice lasts until the very end of the J-wave [16; 31]. To address this problem, we studied two QRS segments: one ending at J-peak, and another ending at J-end.…”
Section: Discussionmentioning
confidence: 99%